To Divide or Invade: A Look Behind the Scenes of the Proliferation-Invasion Interplay in the Caenorhabditis elegans Anchor Cell - Lattmann, Evelyn; Deng, Ting; Hajnal, Alex (Frontiers in Cell and Developmental Biology, 2021)
Cell invasion is defined by the capability of cells to migrate across compartment boundaries established by basement membranes (BMs). The development of complex organs involves regulated cell growth and regrouping of different cell types, which are enabled by controlled cell proliferation and cell invasion. Moreover, when a malignant tumor takes control over the body, cancer cells evolve to become invasive, allowing them to spread to distant sites and form metastases. At the core of the switch between proliferation and invasion are changes in cellular morphology driven by remodeling of the cytoskeleton. Proliferative cells utilize their actomyosin network to assemble a contractile ring during cytokinesis, while invasive cells form actin-rich protrusions, called invadopodia that allow them to breach the BMs. Studies of developmental cell invasion as well as of malignant tumors revealed that cell invasion and proliferation are two mutually exclusive states. In particular, anchor cell (AC) invasion during C. elegans larval development is an excellent model to study the transition from cell proliferation to cell invasion under physiological conditions. This mini-review discusses recent insights from the C. elegans AC invasion model into how a G1 cell-cycle arrest is coordinated with the activation of the signaling networks required for BM breaching. Many regulators of the proliferation-invasion network are conserved between C. elegans and mammals. Therefore, the worm may provide important clues to better understand cell invasion and metastasis formation in humans.